Analisis Pelaksanaan Evaluasi Pembelajaran Sosiologi Berbasis E-Learning Moodle - Wiken Sandhira (Jurnal Ilmu Sosial dan Humaniora, 2026)
This research aims to determine the planning, implementation, and results of the evaluation of Sociology learning based on Moodle e-learning. The method used is descriptive qualitative. Data collection techniques used are observation, interviews and documentation. Data analysis techniques used are data reduction, data presentation, and drawing conclusions. The analysis in this study is presented descriptively using five informants, namely one Sociology subject teacher and four students of class X D of SMA Negeri 1 Pontianak. The results of the study indicate that in planning the evaluation of sociology learning based on Moodle e-learning, teachers prepare outlines and questions according to competency achievements, cognitive levels, cognitive domains of sociology learning. In the implementation of the learning evaluation, students carry out direct evaluation activities based on Moodle e-learning which include the preparation stage of logging in to the account, working on questions and submitting questions. Evaluation in this context aims to measure the achievement of student understanding based on aspects of knowledge regarding the sociology subject matter that has been studied.